Telemedical treatment of diabetic foot ulcer in rural and remote areas: a prospective single centre randomised controlled clinical trial - Usman H Malabu; Venkat N Vangaveti; Julie Goodall; Jacqueline Bulbrook; Erik Biros; Harshal Deshmukh; Kunwarjit S Sangla (Diabetology & Metabolic Syndrome)
Abstract Objectives The role of telemedical treatment for patients with diabetic foot ulcers residing in rural areas remains uncertain. Therefore, our objective was to conduct a randomized controlled trial comparing the effectiveness of telemedical treatment in rural settings with the standard tertiary healthcare approach for managing diabetic foot ulcers. Methods The study was conducted between 2016 and 2022. Participants were randomly assigned 2:1 to either face-to-face usual care (UC) group or telemedical treatment group. The protocol for the telemedical treatment group involved fortnightly consultations conducted by a locally trained nurse in the patients’ rural hospital over 12 weeks compared to similar protocol for face-to-face podiatrist-treated UC group. The primary endpoints were complete healing of the ulcer or limb amputation while secondary outcomes included circulating markers of inflammation as a marker of wound healing. Results One hundred and fifty-one participants out of 232 met the inclusion criteria and 50 were randomised to telemedical treatment group and 101 to the UC group. The clinical and demographic characteristics of the participants were similar in both groups. Following 12 weeks of treatment, we observed that complete ulcer healing was achieved in 16 out of 50 individuals (32%) in the telemedical treatment group, while 28 out of 101 individuals (28%) in the UC group achieved the same outcome (p = 0.58). Amputation rates were 23% (11/50) in the telemedicine and 25% (23/101) in the UC group (p = 0.080). Conclusions Our study found no statistically significant differences in wound healing (32% vs. 28%, p = 0.58) or amputation rates (23% vs. 25%, p = 0.80) between nurse-led telemedicine in rural settings and usual care for diabetic foot ulcers over 12 weeks. This promising result suggests that telemedicine could be a viable option for rural patients; however, further research exploring other clinically relevant endpoints and vulnerable subgroups is needed to solidify its role. The known Diabetic foot ulcers pose a significant burden on rural and remote communities with limited access to specialists’ care and high limb amputation rates. The new Our randomised controlled trial demonstrated that nurse-led telemedicine in rural hospitals is equally effective as podiatrist care in tertiary hospitals for healing diabetic foot ulcers within 12 weeks. Key ulcer measurements and wound healing biomarkers further support this finding. The implications Telemedicine offers a viable solution for management of diabetic foot ulcer in rural and remote areas. It has the potential to enhance patient outcomes and significantly reduce healthcare disparities.